New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry, Marimuthu & Rajan, 2019 - Parameswaran, Usha V.; Mohammed Nowshad, B.; Dixit, Sudhanshu; Manjebrayakath, Hashim; Idreesbabu, K.k.; Saravanane, N. (Zootaxa, 2020)
The paper presents three new records of brittle stars for Indian waters, collected from the Lakshadweep atolls (northern Indian Ocean)—Ophiarachnella septemspinosa (Müller & Troschel, 1842), Ophiocoma cynthiae Benavides-Serrato & O’Hara, 2008 & Ophiomoeris obstricta (Lyman, 1878). Further, this paper also discusses the validity of two recently described taxa from this archipelago, the genus Indophioderma with the species Indophioderma ganapatii Sastry, Marimuthu & Rajan, 2019. A checklist of brittle stars reported so far from the Lakshadweep Islands is provided, which includes 40 valid species—32 from shallow (reef) areas and 8 deep-sea (>200m) species.